Acrolein Promotes Aging and Oxidative Stress via the Stress Response Factor DAF-16/FOXO in Caenorhabditis elegans - Jiaqian Hong; Yiming Song; Jiayan Xie; Jianhua Xie; Yi Chen; Ping Li; Danyang Liu; Xiaobo Hu; Qiang Yu (Foods, 2022)
For this investigation, Caenorhabditis elegans (C. elegans) served, for the first time, as a model organism to evaluate the toxic effect and possible underlying mechanisms under acrolein (ACR) exposure. The results showed that ACR exposure (12.5–100 μM) shortened the lifespan of C. elegans. The reproductive capacity, body length, body width, and locomotive behavior (head thrash) of C. elegans were diminished by ACR, especially the doses of 50 and 100 μM. Furthermore, ACR significantly enhanced the endogenous ROS levels of C. elegans, inhibited the antioxidant-related enzyme activities, and affected the expression of antioxidant related genes. The increasing oxidative stress level promoted the migration of DAF-16 into the nucleus that was related to the DAF-16/FOXO pathway. It was also confirmed by the significant decrease of the lifespan-shortening trend in the daf-16 knockout mutant. In conclusion, ACR exposure induced aging and oxidative stress in C.elegans, resulting in aging-related decline and defense-related DAF-16/FOXO pathways’ activation.